Innovation platforms as a tool for improving agricultural production: The case of Yatenga province, northern Burkina Faso - Teno, G.; Cadilhon, Joseph J. (2016)
Innovation platforms are a development tool used increasingly to support the stakeholders in complex systems for agricultural development in developing countries. This article presents the results of a study measuring the impact of innovation platforms on improving agricultural production for the beneficiaries of a project in Yatenga province, northern Burkina Faso. This innovation platform was installed in 2011 as part of the activities of the Volta2 project, operating jointly in Burkina Faso and Ghana. The results of surveys using Likert scales to quantify the project beneficiaries’ perceptions and qualitative surveys of the various partners revealed that there was an improvement in agricultural production. This improvement has been attributed to the Volta2 project’s innovation platforms, which enabled an increase in the beneficiaries’ social and human capital, empowering them to seek and find local solutions adapted to their problems.